Nanotube-supported bioproduction of 4-hydroxy-2-butanone via in situ cofactor regeneration - Jiang, Rongrong (2013)
Nicotinamide cofactor-dependent oxidoreductases have been widely employed during the bioproduction of varieties of useful compounds. Efficient cofactor regeneration is often required for these biotransformation reactions. Herein, we report the synthesis of an important pharmaceutical intermediate 4-hydroxy-2-butanone (4H2B) via an immobilized in situ cofactor regeneration system composed of NAD+-dependent glycerol dehydrogenase (GlyDH) and NAD+-regenerating NADH oxidase (nox). Both enzymes were immobilized on functionalized single-walled carbon nanotubes (SWCNTs) through the specific interaction between the His-tagged enzymes and the modified SWCNTs. GlyDH demonstrated ca. 100% native enzyme activity after immobilization. The GlyDH/nox ratio, pH, and amount of nicotinamide cofactor were examined to establish the optimum reaction conditions for 4H2B production. The nanoparticle-supported cofactor regeneration system become more stable and the yield of 4H2B turned out to be almost twice (37%) that of the free enzyme system after a 12-h reaction. Thus, we believe that this non-covalent specific immobilization procedure can be applied to cofactor regeneration system for bioconversions.